Effects of using double elastic inclined fins on cooling of protruding heated electronic equipment mounted in a bifurcating channel under nano-enhanced magneto forced convection: Computational analysis and optimized configurations - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2025)
New cooling methods and alternate thermal management techniques are needed to improve performance of battery integrated systems, photovoltaic panels and electronic cooling. The miniaturization of electronic devices and higher processing demands result large amount of dissipated heat in a small volume which should be removed as effective as possible. This study proposes a new cooling system by using double elastic inclined fins and nano-enhanced magnetic field for cooling of two hot block which are installed in a T-shaped branching channel. FEM is used to investigate the effects of magnetic field strength (Hartmann number-Ha between 0 and 40), inclination of magnetic field (theta 1 between 0 and 90), inclination of first elastic fin (01 between 0 and 135), and inclination of second elastic fin (02 between -45 and 30) on the field of flow, thermal field, and cooling performance features. Using rigid fins improves cooling performance by 50% and 29% for walls W1 (first block front wall) and W2 (first block top wall) for the strongest magnetic field. When different magnetic field strength cases are compared, cooling rate degradation for hot surface W3 (first block rear wall) is 67% and 19% when elastic and rigid fins are used. The cooling performance of block in vertical channel improves with the use of a rigid fin. Higher magnetic field inclination generally results in cooling performance deterioration for walls of the block in the horizontal channel while trend is opposite for walls of the block in the vertical channel. Reduction of heat transfer up to 47% is obtained for hot wall W1 of horizontal block and it is reduced by about 67% for W4 (second block front wall) with varying inclination. Additionally, fin tilt of double elastic fins affects the cooling effectiveness of the heated blocks in both channels. The optimized scenario improves cooling performance by 254% for elastic fins and 195% for rigid fins when compared to reference configuration of using no-fin with pure fluid.
Keywords: Double elastic fin; T-channel; Magnetic field; Optimization; Hybrid nanofluid; Electronic cooling